PERFORMANCE ANALYSIS OF POSITIONING WITH MULTI GNSS SATELLITES FOR CADASTRAL APPLICATIONS IN DENSE POPULATION AREAS - Adnan Naufal, Alvaz
The Global Navigation Satellite System (GNSS), is a system of satellite constellations orbiting the earth that transmits signals to users so that can be used to determine three-dimensional positions on the earth's surface. The application of Global Navigation Satellite Systems (GNSS) in the land sector (cadastral) is to determine the benchmark of land registration, determine the positions of land parcel boundary points, reconstruct land parcel boundary points, and search for land parcel locations. Regarding the measurement of land parcel boundaries and benchmark in dense population areas, there are several problems or negative impacts that arise due to the density of settlements, one of which is the difficulty in determining the coordinates of land parcel boundary points and measuring benchmark because the parcel boundaries are closed by the roof of the building and attached between the plots of land with one another. Thus, the purpose of this study is to determine the optimal performance, method, and strategy for observing with multi-GNSS satellites in determining the coordinates of land parcel boundary points and the benchmark of land registration in densely populated areas focusing on comparisons between parcel boundary measurements land using the real time method using a receiver equipped with tilt compensation (GNSS/INS Integration) with the measurement of land parcel boundaries using the real time method using a receiver equipped with tilt compensation and a camera (GNSS + visual positioning). The positioning method used is the static method to determine benchmark, the RTK and RTPPP methods to measure land parcel boundaries. The observation strategy used was using the GNSS/INS integration principle for measurement 1 and the GNSS + visual positioning principle for measurement 2. The research was conducted by measuring the four land parcel boundary points, namely A, B, C, and D points. Based on the results of data acquisition and data processing carried out by the author, the results of the parcel boundary coordinates with the best 3D coordinate quality were in measurement 2 with the RTK positioning method, the 3D coordinate quality of point A value is 0.0081 Meters; point B is 0.0091 Meters; point C is 0.0103 meters; and point D is 0.0151 Meters, so that the optimal measurement/positioning strategy for cadastral applications in the form of measuring land parcel boundaries in densely populated areas is a measurement strategy with a receiver equipped with a camera and tilt compensation (GNSS + visual positioning) using the Real time Kinematic positioning method.